Antara Inovasi dan Eksploitasi: Strategi Menghadapi AI Face Swap dalam Deepfake Pornografi Non Konsensual melalui website AI detector berbasis Pendekatan Restorative Justice - Laula Albiya; Jessica Priscilla Pardede; Syifa Raudia Syahputri; Muhammad Adymas Hikal Fikri (PT. Saha Kreasi Indonesia, 2025)
The development of artificial intelligence (AI), particularly face swap technology, has provided significant benefits while also generating new forms of digital crime, namely non-consensual deepfake pornography. This practice constitutes a serious violation of privacy, human dignity, and victim protection, especially affecting women and children. This research aims to develop an innovation and exploitation-prevention strategy through the creation of an AI detector website based on a restorative justice approach. The study employs a Research and Development (R&D) method using the Four-D model (Define, Design, Develop, Disseminate). It integrates technical deepfake detection mechanisms, artificial intelligence ethics, and a legal framework oriented toward victim recovery. The expected outcome is an AI detector website that is effective, ethical, and justice-oriented, while also serving as an alternative model for handling digital sexual crimes beyond purely punitive measures. This research contributes to strengthening legal protection and fostering a safer, fairer, and more ethical digital environment in Indonesia.